Sosialisasi peranan sertifikat halal bagi masyarakat Kelurahan Kampung Baru, Kecamatan Senapelan, Kota Pekanbaru - Irdha Mirdhayati; Wieda Nurwidada H. Zain; Eko Prianto; Muhammad Fauzi (Unri Conference Series: Community Engagement, 2020)
The purpose of this community service was to provide knowledge and understanding of halal certificates to the public, increase public awareness of the importance of halal certificates and motivate the community to have halal certificates for those who have businesses in the scope of halal products. The service method was carried out by socializing the role of the halal certificate, giving questionnaires to participants and evaluating the questionnaire. The parameters of public halal awareness are reviewed from general knowledge about halal law, public awareness about the implementation of halal products and knowledge about the role of halal certificates. The results showed that all participants had good general knowledge of halal law, had high level of awareness of the implementation of the use of halal products and all participants have good knowledge about the role and management of halal certificates. The results of direct discussions with participants explained that micro business actors do not have a halal certificate due to the lack of socialization regarding halal certificate management by the Government. It can be concluded that basic knowledge of halal law and high awareness of halal are not sufficient to guarantee the high desire of micro-entrepreneurs to apply for halal certificates.